Australian treatment outcome study: protocol for the 18–20-year follow-up of a prospective longitudinal cohort examining the natural history of heroin dependence and associated mortality, psychiatric and physical health, and health service use. Issue 7 (12th July 2020) - Marel, Christina; Mills, Katherine; Visontay, Rachel; Wilson, Jack; Darke, Shane; Ross, Joanne; Slade, Tim; Haber, Paul S; Haasnoot, Katherine; Keaveny, Madeleine; Tremonti, Chris; Teesson, Maree
Abstract : Introduction: Opioid dependence is a global health priority, currently making the biggest contribution to drug-related deaths. The chronic, long-term persistence of heroin dependence over the life course requires investigation in prospective longitudinal studies, to better understand patterns and predictors of remission and relapse, as well as the impact of changes in substance use on a range of physical and mental health outcomes. Such knowledge is critical in order to identify modifiable risk factors that can be targeted for intervention. Crucial unanswered questions include the following: What are the long-term rates of mortality? What are the long-term patterns and predictors of heroin use, remission, psychiatric health and health service use? What are the long-term physical health consequences of heroin use? Methods and analysis: The 18–20-year follow-up of the Australian Treatment Outcome Study (ATOS) cohort will examine the natural history of heroin dependence of an existing cohort of 615 people with heroin dependence, who were recruited into the study in 2001–2002. Five waves of follow-up interviews have since been completed, at 3-month, 1-year, 2-year, 3-year and 10–11-year post-baseline. At the 18–20-year follow-up, the ATOS cohort is (on average) approaching their 50s and an average of 30 years have passed since they first used heroin. The 18–20-year follow-up will consist of: (1) a structured interview; (2) physical health assessment; and (3) data linkage. The results of this follow-up will improve our understanding and management of age-related disorders in this population, which if not addressed in the immediate future, has the capacity to overwhelm treatment centres and aged care facilities. Ethics and dissemination: Ethical approval has been granted for the study (Sydney Local Health District Royal Prince Alfred Zone, Human Research Ethics Committee X18-0512 & HREC/18/RPAH/733). The results of the study will be disseminated through published manuscripts, bulletins and technical reports, as well as conference, seminars, webinar and workshop presentations.